Rodzina i młodzież. Teoria i badania - Kwak, Anna (Wydawnictwo Naukowe UAM, 2008)
Presen ted article is ad dressed to re ad e rs interested in two topics. Firstly, it attempts to show w ha t are the main points of studies referring to bond between adolescents and its family. S econdly, it tries to p re sen t in w h a t extent theories in the question constitute basis for research . The question lies in the p roblem w he th e r re s e arch es n ot based on theories a re valuable?
Family and youth. Theory and research